2023
DOI: 10.1002/ctm2.1405
|View full text |Cite
|
Sign up to set email alerts
|

METTL3‐mediated m6A modification of circPRKAR1B promotes Crohn's colitis by inducing pyroptosis via autophagy inhibition

Jie Zhao,
Zhibin Zhao,
Pu Ying
et al.

Abstract: BackgroundThe roles of circRNA and N6‐methyladenosine (m6A) methylation in Crohn's disease (CD) have drawn much attention. Therefore, this investigation aimed to discover how the m6A modification of circRNAs contributes to CD progression.MethodsThe study performed circRNA sequencing on colon samples from four CD patients and four normal controls (NCs) to screen for dysregulated circRNAs. Quantitative real‐time polymerase chain reaction (qRT‐PCR) was performed to validate the candidate circRNA expression and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Additionally, Hu et al propose that WTAP-mediated m6a modification contributes to improved stability for circCCAR1 [ 24 ]. Furthermore, METTL3 has been observed regulating various circRNAs such as cirRIMS2 [ 25 ], circPRKAR1B [ 26 ], and cirQSOX1 [ 27 ] through its involvement in mediating m6A methylation. Considering these findings, we hypothesized that circFTO may interact with MTC to influence self-methylation or modifying other RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Hu et al propose that WTAP-mediated m6a modification contributes to improved stability for circCCAR1 [ 24 ]. Furthermore, METTL3 has been observed regulating various circRNAs such as cirRIMS2 [ 25 ], circPRKAR1B [ 26 ], and cirQSOX1 [ 27 ] through its involvement in mediating m6A methylation. Considering these findings, we hypothesized that circFTO may interact with MTC to influence self-methylation or modifying other RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…A comparative study showed that necroptosis is active in children with CD and can strengthen the inflammatory process 6 . Aggravation of NLRP3 inflammasome-mediated pyroptosis promotes Crohn’s colitis and gasdermin-E-mediated pyroptosis is involved in CD pathogenesis through the release of proinflammatory cytokines 7 , 8 . There is evidence at the single-cell transcriptome level that ferroptosis participates in the imbalance of intestinal microenvironment homeostasis in CD patients and inhibition of ferroptosis can reconstruct intestinal barrier 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%